étoile: a fashion branding project. - Wong, Hanni. (2011)
The advancement of the 21st century woman presents a familiar conundrum: The balance of work and life. Based on the principle of balance, étoile is a mid-range fashion brand targeted at working females, which seeks balance in a woman’s wardrobe, celebrating her femininity.